Distribution of titanium diboride microparticles introduced into aluminum ingot by MHD-stirring of a crystallizing melt - Khripchenko, Stanislav Yurievich; Dolgikh, Veniamin Mikhaylovich; Siraev, Ramil’ Rifgatovich (Computational Continuum Mechanics, 2023)
The paper presents a method for incorporating titanium diboride TiB2 microparticles 1-5 μm in size into aluminum melt А0 by exposing the liquid metal to rotating and traveling magnetic fields. Under the combined action of these fields, numerical simulation is used to study the behavior of macro- and microparticles in a crucible with liquid aluminum. The mathematical and numerical models provide for the solutions of several sub-problems: calculation of the electromagnetic field of the MHD-stirrer and the resulting Lorentz forces in the liquid metal; investigation of the liquid metal flow in the crucible under the action of Lorentz forces, and the formation of its free surface due to the action of the rotating field; determination of the distribution and motion trajectories of macro- and microparticles in the flowing metal. The results of the physical experiments on the injection of TiB2 microparticles into liquid aluminum and its subsequent directional crystallization due to continuous MHD-stirring by the traveling and rotating magnetic fields are described. In the experiments, two ways of introducing microparticles into liquid aluminum were tested: in the first variant, reinforcing particles were injected into molten aluminum as components of pressed pellets containing aluminum microparticles; in the second, the microparticles were initially located at the bottom of the crucible and covered with an aluminum plate, then the crucible was filled with liquid aluminum. The analysis of the physical characteristics of the obtained ingot material and the results of its study by optical and electron microscopy techniques demonstrated that microparticles are almost uniformly distributed in the core of the ingots, which qualitatively agrees with the results of experimental observations.
Keywords: MHD-stirring; numerical experiment; aluminum composite; microparticles; particle distribution; physical experiment